The Profile of Infantile Hypertrophic Pyloric Stenosis in a Tertiary Children's Hospital in Nepal - Basnet, Bal Mukunda; Lacoul, Robal; Singh, Raj Kumar; Simkhada, Prashant; Chaudhary, Gajendra (Journal of Nepal Paediatric Society, 2021)
Introduction: Infantile Hypertrophic Pyloric Stenosis (IHPS) is the most common surgical cause of non-bilious vomiting in infancy and in the developed world. It is more common among male infants with a peak age at presentation of 4 weeks. This study aims to review the mean age at the time of diagnosis, serum electrolyte changes, ultrasonographic pyloric dimensions and surgical outcomes in IHPS at a tertiary children’s hospital in Nepal. Methods: A retrospective chart review of patients with IHPS who presented to Kanti Children’s Hospital between June 2016 and June 2020 was performed. Data on age, sex, laboratory and ultrasonographic dimensions, treatment and outcomes of treatment were collected and analysed. Results: The clinical record of 150 infants were retrieved and analysed who were diagnosed according to the clinical manifestations, laboratory and ultrasound examination from 2016 to 2020. The mean age at presentation was 46.57 ± 27.3 days with male preponderance of 84%. The proportion of IHPS cases with hyponatremia and hypokalemia was 31.3% and 18.0% respectively. The mean pyloric muscle thickness and pyloric length was 5.4 mm and 20.28 mm respectively. All cases were managed with Ramstedt pyloromyotomy with an average length of hospital stay of 5.03 days. There was no mortality and also no significant major complications. Conclusions: This study has shown that IHPS is a common condition in our setting. More attention should be paid to diagnose early. Paediatricians and general surgeons should have high index of suspicion in infants with non-bilious vomiting to avoid delay in diagnosis.